Laboratory Maintenance of the Chytrid Fungus Batrachochytrium dendrobatidis. Issue 12 (6th December 2021) - Prostak, Sarah M.; Fritz‐Laylin, Lillian K.
Abstract: The chytrid fungus Batrachochytrium dendrobatidis ( Bd ) is a causative agent of chytridiomycosis, a skin disease associated with amphibian population declines around the world. Despite the major impact Bd is having on global ecosystems, much of Bd 's basic biology remains unstudied. In addition to revealing mechanisms driving the spread of chytridiomycosis, studying Bd can shed light on the evolution of key fungal traits because chytrid fungi, including Bd, diverged before the radiation of the Dikaryotic fungi (multicellular fungi and yeast). Studying Bd in the laboratory is, therefore, of growing interest to a wide range of scientists, ranging from herpetologists and disease ecologists to molecular, cell, and evolutionary biologists. This protocol describes how to maintain developmentally synchronized liquid cultures of Bd for use in the laboratory, how to grow Bd on solid media, as well as cryopreservation and revival of frozen stocks. © 2021 The Authors. Current Protocols published by Wiley Periodicals LLC. Basic Protocol 1 : Reviving cryopreserved Bd cultures Basic Protocol 2 : Establishing synchronized liquid cultures of Bd Basic Protocol 3 : Regular maintenance of synchronous Bd in liquid culture Alternate Protocol 1 : Regular maintenance of asynchronous Bd in liquid culture Basic Protocol 4 : Regular maintenance of synchronous Bd on solid medium Alternate Protocol 2 : Starting a culture on solid medium from a liquid culture Basic Protocol 5 : Cryopreservation of Bd